Three LysM effectors of Zymoseptoria tritici collectively disarm chitin‐triggered plant immunity. (1st April 2021) - Tian, Hui; MacKenzie, Craig I.; Rodriguez‐Moreno, Luis; van den Berg, Grardy C. M.; Chen, Hongxin; Rudd, Jason J.; Mesters, Jeroen R.; Thomma, Bart P. H. J.
Abstract: Chitin is a major structural component of fungal cell walls and acts as a microbe‐associated molecular pattern (MAMP) that, on recognition by a plant host, triggers the activation of immune responses. To avoid the activation of these responses, the Septoria tritici blotch (STB) pathogen of wheat, Zymoseptoria tritici, secretes LysM effector proteins. Previously, the LysM effectors Mg1LysM and Mg3LysM were shown to protect fungal hyphae against host chitinases. Furthermore, Mg3LysM, but not Mg1LysM, was shown to suppress chitin‐induced reactive oxygen species (ROS) production. Whereas initially a third LysM effector gene was disregarded as a presumed pseudogene, we now provide functional data to show that this gene also encodes a LysM effector, named Mgx1LysM, that is functional during wheat colonization. While Mg3LysM confers a major contribution to Z. tritici virulence, Mgx1LysM and Mg1LysM contribute to Z. tritici virulence with smaller effects. All three LysM effectors display partial functional redundancy. We furthermore demonstrate that Mgx1LysM binds chitin, suppresses the chitin‐induced ROS burst, and is able to protect fungal hyphae against chitinase hydrolysis. Finally, we demonstrate that Mgx1LysM is able to undergo chitin‐induced polymerization. Collectively, our data show that Z. tritici utilizes three LysM effectors to disarm chitin‐triggered wheat immunity. Abstract : Three Zymoseptoria tritici chitin‐binding LysM effectors differentially contribute to virulence by suppressing chitin‐induced host defences or by shielding hyphae against host chitinases through polymerization.